Microalloyed Zn-Mn alloys: From extremely brittle to extraordinarily ductile at room temperature. (15th April 2018) - Shi, Zhang-Zhi; Yu, Jing; Liu, Xue-Feng
Highlights: Brittle as-cast Zn-0.34Mn and Zn-0.76Mn alloys become extraordinarily ductile after hot-rolling, annealing and cold-rolling. Recrystallization of Zn grains happens during hot-rolling and cold-rolling. Quantity of MnZn13 particles has a great influence on textures of Zn grains. Recrystallization of Zn grains stimulated by clusters of MnZn13 particles happens during room temperature tensile test. Graphical abstract: Abstract: Zn-0.34Mn and Zn-0.76Mn alloys transit from extremely brittle in as-cast status to extraordinarily ductile with elongations ranging from 88.8% to 94.0% at room temperature through 83.3% hot-rolling, annealing at 200 °C for 2 h and then air cooling, and finally 84% cold-rolling. Both the hot-rolling and the cold-rolling greatly refine Zn grains, while the annealing changes rolled textures into annealed textures. Grains in the as-cold-rolled alloys are smaller than 3 μm. After tensile testing, Zn grains close to the fracture are predominantly equiaxed rather than elongated. An aggregation or a long band of very fine Zn grains smaller than 1 μm is revealed in regions close to the fracture. The extraordinary ductilities of the alloys owe to fine grains before tensile testing and dynamic recrystallization during tensile testing, which helps to relieve accumulated stress.